Acoustic-driven droplet evaporation: beyond the role of droplet-gas relative velocity. (June 2021) - Offner, Avshalom; Berdugo, Nir; Liberzon, Dan
Highlights: An experimental investigation analyzing the effects of an acoustic field fundamental characteristics - pressure and velocity distribution and the phase between them - on a droplet evaporation rate. Experimental results clearly outline that acoustic-driven evaporation differs from oscillatory motion over a droplet. A new, generalized, correlation increases R 2 for fitting the experimental data from 0.82 to 0.94, when compared with a standard model that only accounts for relative velocity. Abstract: Acoustic waves can be used for high-precision evaporation of droplets, allowing for fine control over the droplet diameter. Previous works considered the acoustic field as simply a means for generating relative velocity u 1 between a droplet and its surrounding gas, which convects heat and mass from the droplet while oscillating. In the present work, we experimentally examine the effects of an acoustic field fundamental characteristics – pressure and velocity distribution and the phase between them – on a droplet evaporation rate. Our results clearly show that the pressure and phase contribute to the evaporation, with the latter dramatically affecting the process. We propose a generalization to existing models that account only for variations in u 1, and demonstrate how the new model outperforms its counterpart when fitted to the experimental data. Our generalized correlation increases R 2 for fitting the experimental data from 0.82 to 0.94, when compared with a standard model that only accounts for relative velocity. The new insight may be utilized for enhancement and fine-tuned control over droplet evaporation via acoustics, to be used over a wide range of applications, including lab-on-a-droplet reactions and vapor transport in thermoacoustic devices.